Dental health and lung cancer risk in the Golestan Cohort Study - Yukiko Yano; Christian C. Abnet; Gholamreza Roshandel; Akua Graf; Hossein Poustchi; Masoud Khoshnia; Akram Pourshams; Farin Kamangar; Paolo Boffetta; Paul Brennan; Sanford M. Dawsey; Emily Vogtmann; et al. (BMC Cancer, 2024)
Abstract Background Poor oral health has been linked to various systemic diseases, including multiple cancer types, but studies of its association with lung cancer have been inconclusive. Methods We examined the relationship between dental status and lung cancer incidence and mortality in the Golestan Cohort Study, a large, prospective cohort of 50,045 adults in northeastern Iran. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for associations between three dental health measures (i.e., number of missing teeth; the sum of decayed, missing, or filled teeth (DMFT); and toothbrushing frequency) and lung cancer incidence or mortality with adjustment for multiple potential confounders, including cigarette smoking and opium use. We created tertiles of the number of lost teeth/DMFT score in excess of the loess adjusted, age- and sex-specific predicted numbers, with subjects with the expected number of lost teeth/DMFT or fewer as the reference group. Results During a median follow-up of 14 years, there were 119 incident lung cancer cases and 98 lung cancer deaths. Higher DMFT scores were associated with a progressively increased risk of lung cancer (linear trend, p = 0.011). Compared with individuals with the expected DMFT score or less, the HRs were 1.27 (95% CI: 0.73, 2.22), 2.15 (95% CI: 1.34, 3.43), and 1.52 (95% CI: 0.81, 2.84) for the first to the third tertiles of DMFT, respectively. The highest tertile of tooth loss also had an increased risk of lung cancer, with a HR of 1.68 (95% CI: 1.04, 2.70) compared with subjects with the expected number of lost teeth or fewer (linear trend, p = 0.043). The results were similar for lung cancer mortality and did not change substantially when the analysis was restricted to never users of cigarettes or opium. We found no associations between toothbrushing frequency and lung cancer incidence or mortality. Conclusion Poor dental health indicated by tooth loss or DMFT, but not lack of toothbrushing, was associated with increased lung cancer incidence and mortality in this rural Middle Eastern population.